2013
DOI: 10.1590/s0102-67202013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Existem benefícios com a cirurgia retardada após radioterapia e quimioterapia neoadjuvante no câncer de reto localmente avançado?

Abstract: Delayed surgery after chemoradiation offered no clear benefits in terms of complete tumor response or downstaging. Predictive molecular factors should be investigated in the future for the proper selection of patients who will benefit from chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The majority of reviewed studies which assessed surgical complications did not find any impact of surgical delay on operative complications [ 7 , 9 , 10 , 28 , 29 , 31 , 36 , 39 , 41 43 , 51 , 57 , 61 ], with two papers finding an increase in complications with later surgery [ 46 , 54 ] and another finding that later surgery decreased anastomotic and wound complications [ 53 ]. Only two of the reviewed studies assessed development of metastatic disease in the context of time to surgery after completion of radiotherapy and neither found significant between group differences [ 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of reviewed studies which assessed surgical complications did not find any impact of surgical delay on operative complications [ 7 , 9 , 10 , 28 , 29 , 31 , 36 , 39 , 41 43 , 51 , 57 , 61 ], with two papers finding an increase in complications with later surgery [ 46 , 54 ] and another finding that later surgery decreased anastomotic and wound complications [ 53 ]. Only two of the reviewed studies assessed development of metastatic disease in the context of time to surgery after completion of radiotherapy and neither found significant between group differences [ 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stein et al [ 5 ] reported 7% higher ypCR rate in the long interval group (p=0.97). In a study by Fang et al [ 19 ] and colleagues, ypCR rate was 6.6% higher in the short interval group (p=0.37). The recently published GRECCAR-6 trial reported that there was no difference in ypCR rate between the 7-week (15%) and 11-week (17.4%) groups (p=0.60) [ 9 ].…”
Section: Discussionmentioning
confidence: 96%